2016
DOI: 10.1007/978-1-4939-3037-1_20
|View full text |Cite
|
Sign up to set email alerts
|

Spot Synthesis: An Optimized Microarray to Detect IgE Epitopes

Abstract: Peptide microarrays have become increasingly more affordable in recent years with the SPOT technique being one of the most frequently used methods for synthesis and screening of peptides in arrays. Here, a protocol is presented for the identification of the amino acid sites involved in the conversion of human IgG to IgE response during the passive administration of therapeutic, anti-snake venom sera. Similarly, the minimal region of both the IgG and IgE binding epitopes, important for its interaction with liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Keeping this consideration in mind, many groups have published extremely exciting results that clearly show that both diagnostic and prognostic indications can be derived from the analysis of the IgE profile directed to peptides of different allergen sources. [77][78][79][80][81][82][83] Of course, the need for large epidemiological studies will be necessary to define rules that can be applied to different populations of patients. However, the possibility of dissecting the immune response mediated by IgE will be included in the fourth diagnostic level of allergic diseases, such as the basophil activation test, in the near future.…”
Section: Available Diagnostic Toolsmentioning
confidence: 99%
“…Keeping this consideration in mind, many groups have published extremely exciting results that clearly show that both diagnostic and prognostic indications can be derived from the analysis of the IgE profile directed to peptides of different allergen sources. [77][78][79][80][81][82][83] Of course, the need for large epidemiological studies will be necessary to define rules that can be applied to different populations of patients. However, the possibility of dissecting the immune response mediated by IgE will be included in the fourth diagnostic level of allergic diseases, such as the basophil activation test, in the near future.…”
Section: Available Diagnostic Toolsmentioning
confidence: 99%
“…Because we predict from the native Ag, we showed that only a limited number of peptides (compared to the diversity generated in phage-display method) is necessary to map discontinuous epitopes. After synthesis, the functionality of the peptides exploring all the surface of the protein could be assessed in a convenient high-throughput recognition assay, such as the SPOT method [35, 44, 45] or other technologies [46]. If the correct sequence is present in the bank, the Ab should recognize it and this identifies the epitope region on the protein.…”
Section: Discussionmentioning
confidence: 99%
“…The entire sequence (728aa) of the non-characterized protein nicastrin, deposited in the UNIPROT (Q4DEM3) and a possible component of GSC in T. cruzi , was represented by a continuous series of 144, 14-residue peptides that overlapped preceding and following peptides by 9 residues. The peptides were synthesized in place on a cellulose membrane according to a SPOT synthesis protocol [ 18 ] using an Auto-Spot Robot ASP-222 (Intavis Bioanalytical Instruments AG, Köln, Germany). Coupling reactions were followed by acetylation with acetic anhydride (4%, v / v ) in N , N -dimethylformamide to render peptides unreactive during the subsequent steps.…”
Section: Methodsmentioning
confidence: 99%